A superior secure key spawn using boosted uniqueness encryption for cloud computing in advanced extensive mobile network - Chandra, G. Rajesh; Mohan, K. Jagan; Khalaf, Osamah Ibrahim; Gopisetty, Guru Kesava Dasu; Anand, Dama; Algburi, Sameer; Lakshmi, S. Vijaya (Universitas Mercu Buana, 2024)
The cloud computing sector, including mobile networks has increased in the present time. Because of advanced features and security related information in cloud. So many methods are available for handling these problems. Cloud security, large number of methods existing for provide security. Among that, so many widespread techniques cast-off to protected data in cloud based on Individuality based encryption. This method specialty is allowing only authorized end users for access legal data and avoid smalevolent attack. Individuality -based encryption method follows up the four stages like Name, Key generation, encryption and decryption. Among these Key generation is most important for generating secure key. It provides unbreakable and non-derivable secure keys to provide strong security. This paper provides a novel approach for providing advanced security called identity-based encryption. This approach uses segment of a bitidentity thread in demandto evade seepage of user’s data identity, if any attacker decodes the key also. Statistical reports show that the proposed algorithm takes less time in the process of decryption and encryption compared to other traditional approaches. One more feature of our novel method is skinning the user’s uniqueness by using parametric curve fitting. It contains a polynomial interpolation function.